The Study of Customer Satisfaction of Shopee Customers In Malaysia - Kah Boon Lim; Yeo Sook Fern; Hardave Singh Kler a/l Bhajan Singh (Research Synergy Foundation, 2021)
The main objective of this study is to investigate the factors affect customer satisfaction level among Shopee customers in Malaysia. A set of self-administered questionnaires has been distributed to 200 targeted Shopee users in three states of Malaysia which are Johor, Melaka and Selangor. The five independent variables, which are price, trust, electronic word of mouth, website quality and security have been tested on their relationship towards the dependent variable, which is consumer satisfaction towards online shopping platform, Shopee in Malaysia. The collected data were keyed into SPSS version 25 and followed by using Partial Least Square Structural Equation Modeling (PLS-SEM 3.2.8) to assess the hypothesis. The result of this research given the feedbacks where trust, electronic word of mouth and website quality have significant effect towards consumers satisfaction on Shopee in Malaysia. However, price and security does not show a significant relationship with Shopee’s consumer satisfaction. In conclusion, this study helps to better understand the consumer satisfaction of Shopee’s online shopping services in Malaysia.